Analisis Risiko Warehouse Management System Dalam Supply Chain Management Di PT. Magnesium Gosari Internasional - Ayu Martha Dinata; Rohmatin Agustina; Arini Roro Anggun (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze risk management in the Warehouse Management System (WMS) within Supply Chain Management at PT. Magnesium Gosari Internasional using the ISO 31000:2009 framework. The research methodology employs a qualitative approach through direct observation, in-depth interviews, and documentation studies. Data analysis was conducted by identifying, assessing, and evaluating risks based on their probability and impact levels. The research identified 21 risks classified into 5 main categories: Receiving, Putaway, Demand, Storage, and Shipment. Of the total identified risks, 7 risks fall into the low-risk category, 5 risks in the medium-risk category, and 9 risks in the high-risk category. This research provides risk treatment recommendations that can be implemented to enhance the effectiveness of risk management in the company's warehouse system.